Telaah Teknis terhadap Kinerja Mutu Perkerasan Jalan Nasional dan Propinsi - Mulyono, Agus Taufik; Riyanto, Bambang (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
National and provincial road networks have a major role to provide high accessibility and mobility to all community. Their services both functional and structural, therefore, need to improve continuously. Current figures show that from 2002 to 2003 the length of the road networks increased 8.07%. During these years, it was found that the road investment increased 28.61% and AADT increased 8.80%.  However, it was not followed by the road networks performance, such as the IRI increased 39.5%, the road networks with SDI>50 increased 84.01%, and the road network in bad condition increased 64.92%.  The purpose of this paper is to highlight and review technical aspects of the road networks performance particularly their quality standard achievement. Finally this paper discusses reasons of decreased quality performance of the road networks whilst increased investment and maintenance cost occurred. Keyword:   technical review, pavement quality, IRI, SDI, investment, national and provincial roadPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3902[How to cite: Mulyono, A.T. dan Riyanto, B., 2005, Telaah Teknis terhadap Kinerja Mutu Perkerasan Jalan Nasional dan Propinsi, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 108-118]